2019
DOI: 10.1002/imhj.21774
|View full text |Cite
|
Sign up to set email alerts
|

Parenting self‐efficacy in the context of poverty and HIV in Eastern Uganda: A qualitative study

Abstract: We sought to understand social representations of effective parenting and parenting self‐efficacy among female HIV‐affected caregivers in rural Eastern Uganda. We conducted in‐depth interviews (n = 21) to describe parenting experiences and caregivers’ perceptions of their own parenting abilities and to create vignettes for use in directed focus groups. We carried out open focus groups (n = 2) to gain social perspectives on parenting, and directed focus groups (n = 2) concentrated on parenting self‐efficacy. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Another study in Ghana reported stigma among tuberculosis patients, a disease that is usually associated with HIV/AIDS, due to the immunosuppression that arises from it and that stigma could stifle a source of support 53,54 . In this study, support was invariable low for many caregivers and centred on emotional/social support and spirituality and consistent with a study conducted in eastern Uganda 55 . A spectacular example of supporting caregivers points to Ref.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Another study in Ghana reported stigma among tuberculosis patients, a disease that is usually associated with HIV/AIDS, due to the immunosuppression that arises from it and that stigma could stifle a source of support 53,54 . In this study, support was invariable low for many caregivers and centred on emotional/social support and spirituality and consistent with a study conducted in eastern Uganda 55 . A spectacular example of supporting caregivers points to Ref.…”
Section: Discussionsupporting
confidence: 86%
“…53,54 In this study, support was invariable low for many caregivers and centred on emotional/social support and spirituality and consistent with a study conducted in eastern Uganda. 55 CLWHs in this study were not given support for education even though they have poor school attendance and educational delays due to frequent hospital appointments and poor cognitive difficulties. A study in South Africa intimated schools served as support for adolescents living with HIV/AIDS which could be beneficial for CLWH not realized in this study as school authorities were not in the knowledge of the CLWH's predicament.…”
Section: Discussionmentioning
confidence: 92%